2021
DOI: 10.14366/usg.20191
|View full text |Cite
|
Sign up to set email alerts
|

Elastography for the differential diagnosis of malignant versus benign testicular lesions: a meta-analysis

Abstract: Objectives: To evaluate the value of elastography in the differential diagnosis of benign versus malignant testicular lesions. Methods:The PubMed, Cochrane Library, and Embase databases were searched for relevant literature. The diagnostic accuracy of elastography was tested using pooled sensitivity, specificity, likelihood ratio, post-test probability, diagnostic odds ratio, and by summarizing the area under the hierarchical summary receiver operating characteristic (HSROC) curve.Results: Seven studies with 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A significant increase in testicular stiffness was observed with the SWE method in patients with testicular tumors, varicocele and torsion. [17][18][19][20][21] Based on a metaanalysis of studies that used the SWE to distinguish between malignant and benign testicular lesions, the researchers found that the pooled sensitivity was 87% and the pooled specificity was 81%. As a general rule, malignant lesions are considered to be harder than benign lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase in testicular stiffness was observed with the SWE method in patients with testicular tumors, varicocele and torsion. [17][18][19][20][21] Based on a metaanalysis of studies that used the SWE to distinguish between malignant and benign testicular lesions, the researchers found that the pooled sensitivity was 87% and the pooled specificity was 81%. As a general rule, malignant lesions are considered to be harder than benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[22] It should be noted, however, that stiffness measurements of some benign lesions with calcification may be higher and, stiffness measurements of some malignant lesions with necrosis and liquefaction may be lower. [17] In varicoceles, stiffer testicles are thought to be associated with germ cell atrophy, thickened tubular basement membranes, and increased interstitial fibrosis. [18] In both animal and human studies, testicular torsion has been associated with increased testicular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…After routine plain scanning, iodohexanol injection was carried out. Combining high-pressure injectors for injection work, select intravenous injection method with a flow rate of 3ml/s, and perform enhanced scanning [2] . When conducting ultrasound diagnosis, combined with color Doppler ultrasound, exploration work needs to be carried out on the thyroid gland and surrounding tissues in the patient's neck position.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Calcified nodules are usually benign, but may also be one of the manifestations of thyroid cancer. This condition is usually found in ultrasound examination, and the calcified substances are distributed in dots, spots, or masses [2] . The symptoms of thyroid calcified nodules are usually no obvious discomfort, but some patients may experience thyroid enlargement, compression, or local pain.…”
Section: Introductionmentioning
confidence: 99%
“…However, an issue of overlapping results in these pathologies has been reported. The main causes of overlapping results were the presence of calcifications in benign lesions and necrosis/liquefaction in advanced malignant testicular masses [ 67 ]. Various degrees of stiffness can be obtained in large testicular tumors as seen in Figure 5 .…”
Section: 2 Testiclementioning
confidence: 99%